THE RELATIONSHIP BETWEEN CHILD LIKING STATUS AND EMPATHIC TENDENCY OF NURSING STUDENTS - BEKAR, Pınar; ERGEZEN, Yahya; EFE, Emine (Göbeklitepe Medical Science Journal, 2024)
This study was carried out to determine the relationship between nursing students' empathic tendencies and their status of liking child. This study, which was carried out in a descriptive and cross sectional type, conducted with 136 third year nursing students who were studying at the Faculty of Nursing of a state university in Turkey in the spring semester of the 2021-2022 academic year, who took the course of child health and diseases nursing and agreed to participate in the study. Data were collected online via Google Forms using the “Personal Information Form, Empathic Tendency Scale, and Barnett Liking of Children Scale”. A positive, significant relationship was found between nursing students’ Empathic Tendency Scale score average and Barnett Liking of Children Scale score average (p < 0.001). In this study, it was determined that as the levels of child liking of nursing students increased, the levels of empathic tendency also increased.